HIV knowledge and sexual risk behaviour of grade 12 learners in the Cape Metropole, Cape Town - Jaars, Cleopatra (Stellenbosch : Stellenbosch University, 2013)
Thesis (MCurr)--Stellenbosch University, 2013.